2021
DOI: 10.3390/ijerph18137125
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Sedentary Behavior, and Weight Status of University Students during the COVID-19 Lockdown: A Cross-National Comparative Study

Abstract: The temporary closure of learning institutions during the COVID-19 pandemic has dramatically reduced the physical activity of students across all ages. Therefore, this study aimed to investigate the prevalence of physical inactivity and the patterns of physical activity among university students in confinement. This cross-sectional study involved 147 Malaysian students and 107 Indonesian students. Body weight before the pandemic and during the pandemic was self-reported by the respondents, and the Internationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 20 publications
2
34
0
1
Order By: Relevance
“…As the COVID-19 pandemic may significantly change our health behaviors [ 32 ], this study specifically identified that university students’ physical activity levels were more affected during the online learning period. While previous studies have shown that 64.6–79.6% of university students could maintain a level of health-enhanced physical activity during lockdown [ 33 , 34 ], there were only 24% of Taiwanese students in this study who could accumulate at least 150 min of MVPA per week during the online learning period. Furthermore, consistent with a recent systematic review showing a reduction in physical activity in university students during lockdown [ 13 ], our participants were significantly physically inactive and only engaged in physical activity for less than 50% of the time that they previously spent during the in-class learning period.…”
Section: Discussionmentioning
confidence: 67%
“…As the COVID-19 pandemic may significantly change our health behaviors [ 32 ], this study specifically identified that university students’ physical activity levels were more affected during the online learning period. While previous studies have shown that 64.6–79.6% of university students could maintain a level of health-enhanced physical activity during lockdown [ 33 , 34 ], there were only 24% of Taiwanese students in this study who could accumulate at least 150 min of MVPA per week during the online learning period. Furthermore, consistent with a recent systematic review showing a reduction in physical activity in university students during lockdown [ 13 ], our participants were significantly physically inactive and only engaged in physical activity for less than 50% of the time that they previously spent during the in-class learning period.…”
Section: Discussionmentioning
confidence: 67%
“…Students that live with their family members have a high tendency to consume home-cooked meals rather than dining in at restaurants [ 23 ]. In Malaysia, the COVID-19 outbreak resulted in the transition of the physical lectures in universities into virtual lectures [ 24 , 25 ]. Hence, many undergraduates may have returned to their homes and stayed with their family members.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the COVID-19 pandemic has indirectly increased sedentary behaviors among students given that they have been required to study online instead of studying in a physical classroom ( 34 , 35 ). In other words, university students have been forced into sedentary lifestyles because of COVID-19.…”
Section: Introductionmentioning
confidence: 99%